ACCRUED DEPRECIATION AND THE UTILITY RATE BASE IN PENNSYLVANIA. - Buckwlter, W. Roy (The Accounting Review, 1942)
Abstract The purpose of this article is to analyze the weight assigned to accrued depreciation by the Pennsylvania Commission in ascertaining the rate base, and the methods used in determining the amount of accrued depreciation. The Pennsylvania Commission's statement made in 1935, in a case where it determined annual depreciation allowance by the sinking-fund method, that "It is a well established rule as shown by the decisions of the United States Supreme Court, that accrued depreciation must be deducted from a reproduction cost estimate" indicated that the Commission's policy with respect to accrued depreciation where the sinking fund method of accruals was used was founded on the rule of the United States Supreme Court rather than upon a consideration of the economic aspects of the case. In the few cases where the original cost figure was accepted by the Commission as the fair value no deduction was made for accrued depreciation. Numerous cases can be cited which hold that accrued depreciation should be deducted from actual or original cost.